Bapx1 is required for jaw joint development in amphibians. Issue 6 (30th August 2018) - Lukas, Paul; Olsson, Lennart
Abstract : The acquisition of a movable jaw and a jaw joint are key events in gnathostome evolution. Jaws are derived from the neural crest derived pharyngeal skeleton and the transition from jawless to jawed vertebrates consists of major morphological changes, which must have a genetic foundation. Recent studies on the effects of bapx1 knockdown in fish and chicken indicate that bapx1 has acquired such a role in primary jaw joint development during vertebrate evolution, but evidence from amphibians is missing so far. In the present study, we use Ambystoma mexicanum, Bombina orientalis, and Xenopus laevis to investigate the effects of bapx1 knockdown on the development of these three different amphibians. Using morpholinos we downregulated the expression of bapx1 and obtain morphants with altered mandibular arch morphology. In the absence of bapx1 Meckeĺs cartilage and the palatoquadrate jaw joint initially develop separately but during further development the joint cavity between both fills with chondrocytes. This results in the fusion of both cartilages and the loss of the jaw joint. Despite this the jaw itself remains usable for feeding and breathing. We show that bapx1 plays a role in jaw joint maintenance during development and that the morphants morphology possibly mirrors the morphology of the jawless ancestors of the gnathostomes.